(untitled) (Bangladesh Journal of Medical Science, 2018)
Objectives: Both hypercoagulable and hypocoagulable states have been proposed for hypothyroidism, whether in overt or subclinical spectrum. The status of haemostatic functions, metabolic profile and their relationship in hypothyroid disorders need to be evaluated. Methods and Material: This prospective case control study was undertaken in 30- 50 years old female subclinical and hypothyroid patients. Haemostatic functions like bleeding time (BT), clotting time (CT), prothrombin time (PT), activated partial thromboplastin time (APTT), platelet count and metabolic parameters like plasma glucose and lipid levels and clinical variables like blood pressure and body mass index were noted and compared. In addition the strength of correlation of TSH, T4, T3, lipid profile with the haemostatic functions was evaluated. Results: Both groups of patients were obese, normotensive with normal haemostatic parameters. The platelet count correlated with TSH in subclinical hypothyroid patients and with T4 levels in hypothyroid patients. Although within normal range, total cholesterol and LDL cholesterol levels were higher and postprandial plasma glucose (PPPG) levels lower in hypothyroid patients compared to subclinical hypothyroid patients. A positive correlation was seen between TSH and LDL, PPPG levels, between fT3 and BMI, and also of antiTPO with total cholesterol, LDL, Fasting plasma glucose (FPG) in hypothyroid patients. The BMI was negatively associated with fT3 levels in subclinical hypothyroid patients. Conclusion: This study found normal haemostatic and metabolic functions in both subclinical and hypothyroid patients. Although within normal range, hypothyroid patients had higher total and LDL cholesterol. TSH and antiTPO levels correlated with LDL levels in these patients. Correlation of platelet count with TSH in subclinical hypothyroid and T4 levels in hypothyroid patients advocate a difference in mechanism involved. Therefore it can be connoted that thyroid status influences metabolic profile, and platelet count. Bangladesh Journal of Medical Science Vol.17(4) 2018 p.532-536